The impact of long-term orientation on compulsive buying behavior: A cross-cultural study - Wang, Pei; Zhai, Yuqing (Frontiers in Psychology, 2022)
The overall purpose of this study was to investigate the wider impacts of cultural values on consumer compulsive buying from a cross-cultural perspective. This study considers the long-term orientation as an extended antecedent to explore the moderating role of materialism value and money attitude on compulsive buying behavior in different cultures. Survey results from 313 Chinese and 309 U.S. consumers indicate that the higher materialistic values drive compulsive buying though some differences exist between consumers in both countries. To specify, American buyers had a higher materialistic orientation and higher compulsive buying tendencies than Chinese consumers. Furthermore, the results indicate that money attitudes are negatively related to compulsive buying behaviors among two countries' consumers. Lastly, this study found that long-term orientations were found to significantly influence money attitudes and compulsive buying among Chinese consumers.